Omnidirectional Stretchable Inorganic-Material-Based Electronics with Enhanced Performance - Kumaresan, Yogeenth; Kim, Hyeonghun; Pak, Yusin; Poola, Praveen Kumar; Lee, Ryeri; Lim, Namsoo; Ko, Heung Cho; Jung, Gun Young; Dahiya, Ravinder (WILEY, 2020)
Inorganic material-based devices are well known for their high performance, excellent stability, and hence suitability for fast computation and communication. But their nonflexibility and nonstretchability often hinder their application in several emerging areas where conformability with irregular 3D surfaces is required in addition to the high performance. Herein, with honeycomb like patterns, the omnidirectional stretchability and conformability of inorganic material-based device are demonstrated without sacrificing the performance. The simple method presented here facilitates the transfer of patterned inorganic material-based devices from rigid poly(methyl methacrylate) (PMMA)/glass substrate onto flexible/stretchable substrate such as polydimethylsiloxane simply by placing a water droplet at the PMMA/glass interface. As a proof of concept, the intrinsically brittle indium-gallium-zinc oxide (IGZO)-based stretchable photodetector devices are fabricated. These devices can be stretched up to 10% without performance degradation, which is a significant improvement considering the less than approximate to 1% fracture limit of IGZO. With Au decoration, these devices show 127-fold higher responsivity (295.3 mA W-1) than planar IGZO devices. The higher fracture strain together with the omnidirectional stretchability underpinned by the honeycomb pattern could allow presented devices to conform to complex hemispherical surfaces such as the human eyes, thus showing significant potential for future high-performance stretchable electronics.